(untitled) (International Journal of Biology and Chemistry, 2015)
The present study aimed to determine the mechanisms of bioaccumulation and decontamination of Polychlorinated biphenyls (PCBs) and Dichlorodiphenyltrichloroethane (DDT) in the body of two-humped camels Camelus bactrianus. The experiment has been carried out in Suzak region of South Kazakhstan. Four lactating two humped camels received 0.8 mg of indicator PCBs (1.3 μg/kg body weight) and DDT 0.12 (DDT 0.2 μg/Kg body weight) mg per camel/day during two months and followed by a 4-month decontamination period. Milk and hump fat of experimental camels have been sampled. Milk samples were analyzed using a liquid-liquid and hump fat using solid extraction by gas chromatography and mass spectrometry method. Concentrations of PCBs and DDT in milk and hump reached a plateau at the end of the 2 months exposure period. Transfer rates into milk ranged between 2% for PCB 101 and 71 % for PCB 180 of the daily dose, which was generally lower than rates observed in ruminants. In the same time, the most important part of the contaminants has been stored in the humps. At the end of experimentation, the total quantity of PCBs excreted in milk was estimated to 28.6 μg and the total quantity accumulated during the contamination period in humps was 5530 μg. Despite a huge variability between the different congeners of iPCBs, the intermediate storage of lipophilic compounds in the humps reduced the concentrations excreted in milk but on the other hand would extent the duration of the decontamination period in comparison with ruminants.